Implementation of Islamic Bank Information Systems for UMKM - Rendi Setiawan Purba (Jurnal Ekonomi, Manajemen, Bisnis dan Akuntansi Review, 2022)
The purpose of this study was to examine the influence of Islamic banking information system software on MSMEs. information structures in Islamic banks that use era to assist operations and control, Islamic banks offer financing to MSME actors in running or developing their business. The research method uses a literature review with research results explaining that Islamic banks are able to provide a very good influence on MSME business financing. Financing in Islamic banks is also an opportunity capital for MSME business development.